Corporate Ethical Identity Perbankan Syariah di Indonesia - Budi Sukardi Taufiq Wijaya (TSAQAFAH, 2013)
This article describes the extent of Islamic Banking in Indonesia in function as an agent of development through ethical identity disclosure in annual reports of Islamic Banking. The importance ethical identity of the company as a part of the personality in the achievement of business objectives, has the purpose to describe the manifestations and uniqueness in order to operate well and success in the market, able to provide recognition and distinction between banks, as an important aspect of the bank’s market competitiveness of sustainable, which includes an understanding of the ethical and social culture of the bank. Islamic banking as a financial institution which different with conventional banks, have a view applies fundamental concepts of property rights and contracts that govern behavior, ethical, moral and social economy, both individuals, institutions, communities and countries. Fundamental perspective above, will be able to belief in religion (Islam), as well as support for Islamic Banks to be integral and system economic of Islam will be applicable in all times and in particular contribute for national economy, as well as being an alternative system for the development of the world economy.